A atuação do pedagogo na empresa: o saber fazer para além da instituição escolar de ensino básico - Silva, Iagliana Do Nascimento (2016)
This work, entitled “THE PEDAGOGUE’S PERFORMANCE IN THE COMPANY: THE KNOW-HOW IN ADDITION TO THE EDUCATIONAL INSTITUTION OF BASIC EDUCATION” was held with teaching professionals in companies SENAI / RN (national service for industrial training) and SEBRAE / RN (Brazilian service to support micro and small enterprises), both of them located in Caico city – RN. This, we aimed to understand how the teacher plays its role in vocational education companies analyzing the process and describing its importance. For the theoretical foundation was used Libâneo (2008), Ribeiro (2010), Candinha (2011), Lopes (2011), Abrantes (2012), among others. To perform the data collection was used bibliographical research, document and application of structured questionnaire with open and closed questions about the challenges and the teacher's performance needs of the enterprise. It was notice that the presence of the pedagogue in enterprise environments is necessary because of the teaching learning process that companies promote. So the business pedagogue configured herself as a professional able to act in the educational, methodological and administrative aspects of the courses, programs and projects promoted by these institutions as they develop them, bringing with it benefits such as: professional training and conducting critical analysis of the situations of the courses, projects and programs developed by companies.